2005
DOI: 10.1016/s1015-9584(09)60338-9
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Body Mass Index and Risk of Formation of Breast Cancer in Chinese Women

Abstract: Weight control in obese women may be an effective measure for breast cancer prevention in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 43 publications
3
28
0
Order By: Relevance
“…Concerning anthropometry, it is accepted that higher values of body mass index (BMI) are associated with a reduced risk of BC in premenopausal women and with an increased risk in postmenopausal ones (Lahmann et al, 2004;WCRF, 2007). Absence of association in premenopausal women has been also described for certain anthropometric measures in some populations such as Chinese (Shu et al, 2001;Chow et al, 2005), Japanese (Hirose et al, 2001), or African American women (Hall et al, 2000), different from what has been consistently described in the Western and Caucasian societies. Recently, waist-to-hip ratio was also associated with an increase of risk in premenopausal Nigerian (Okobia et al, 2006) and Asian American women (Wu et al, 2007).…”
Section: Introductionmentioning
confidence: 89%
“…Concerning anthropometry, it is accepted that higher values of body mass index (BMI) are associated with a reduced risk of BC in premenopausal women and with an increased risk in postmenopausal ones (Lahmann et al, 2004;WCRF, 2007). Absence of association in premenopausal women has been also described for certain anthropometric measures in some populations such as Chinese (Shu et al, 2001;Chow et al, 2005), Japanese (Hirose et al, 2001), or African American women (Hall et al, 2000), different from what has been consistently described in the Western and Caucasian societies. Recently, waist-to-hip ratio was also associated with an increase of risk in premenopausal Nigerian (Okobia et al, 2006) and Asian American women (Wu et al, 2007).…”
Section: Introductionmentioning
confidence: 89%
“…After reviewing the full text of these studies in detail, a total of 39 articles, involving 100,452 participants from 14 provinces, municipalities and regions, were included in the final review (Appendix 1). Among these included studies, we identified 6 cohort studies (Li et al, 2005;Shannon et al, 2005;Wang et al, 2006;Dai et al, 2010;Pronk et al, 2011;Shrubsole et al, 2011;) and 33 case-control studies (Lu et al, 1992;Xu et al, 1997;Zhao et al, 1999;Tao et al, 2002;Zou et al, 2002;Zhang et al, 2003;Chow et al, 2005;Lee et al, 2005;Chou et al, 2006;Huang et al, 2006;Li et al, 2006;Jin, 2007;Ma, 2007;Zhang et al, 2007;Kallianpur et al, 2008;Ren, 2008;Wang et al, 2008;Shrubsole et al, 2009;Wang et al, 2009;Zhang et al, 2009;Qian et al, 2010;Shi et al, 2010;Bao et al, 2011;Dai et al, 2011;Leu et al, 2011;Zhang et al, 2011;Hou et al, 2012;Xu et al, 2012;Yu et al, 2012;Wang et al, 2013). According to the NOS items, 11 studies were evaluated as high quality, 25 studies as modest quality, and 3 studies as low quality, respectively.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…The role of body size, defined by body mass index (BMI), waist circumference(WC) and waist-to-hip ratio(WHR), as modifiable risk factors for breast cancer, were considered in several studies in Asian and Western countries [8][9][10][11][12][13][14]. Despite several mechanisms that may explain the role of obesity and abdominal obesity on breast cancer risk that related to hormonal factors and the effect of fatty cytokine in inflammatory process [15][16][17][18][19][20][21][22], the association between BMI and waist circumference, as biomarkers for general adiposity and central obesity, respectively, with breast cancer risk is controversial with respect to menopausal status.…”
Section: Introductionmentioning
confidence: 99%